1986
DOI: 10.2307/1130428
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Infant Temperament, and Parenting Self-Efficacy: A Mediational Model of Postpartum Depression

Abstract: A model of maternal postpartum depression was tested in which difficult infant temperament was construed as a stressor and supportive interpersonal relationships were construed as a protective resource. It was hypothesized that both infant temperamental difficulty and level of social support would affect maternal depression through the cognitive mediation of perceived self-efficacy in the parenting role. Participants were 55 married women who were assessed during pregnancy and again 3 months postpartum. Infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

63
508
13
24

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 694 publications
(608 citation statements)
references
References 0 publications
63
508
13
24
Order By: Relevance
“…Women who perceived that they had a higher level of available support scored significantly lower on measures of PPD, which may imply that it is the feeling of not being alone that is crucial when becoming a mother. This is in accordance with previous research that demonstrates how a sense of a strong social network and the ability to count on others make up the fundamental protective elements of social support (Cutrona and Troutman 1986). Stern (1998) suggests that new mothers show an increased interest for other mothers and seek their company.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Women who perceived that they had a higher level of available support scored significantly lower on measures of PPD, which may imply that it is the feeling of not being alone that is crucial when becoming a mother. This is in accordance with previous research that demonstrates how a sense of a strong social network and the ability to count on others make up the fundamental protective elements of social support (Cutrona and Troutman 1986). Stern (1998) suggests that new mothers show an increased interest for other mothers and seek their company.…”
Section: Discussionsupporting
confidence: 91%
“…While some studies on PPD have examined the effect of general self-efficacy (Howell et al 2006) and maternal selfefficacy on PPD (Coleman and Karraker 1997; Cutrona and Troutman 1986), there are to our knowledge only two studies (Dai and Dennis 2003;Dennis 2003) that have examined how self-efficacy pertaining to breastfeeding relates to PPD. Their primary aim, however, was to assess the validity of the breastfeeding self-efficacy scale (BSES), rather than discuss the relationship between these variables.…”
Section: Social Supportmentioning
confidence: 99%
“…Maternal personality and maternal psychopathology have been identified as contributing factors to infant sleep problems (Coutrona & Troutman, 1986;Field, Healy, Goldstein, Perry, & Bendell, 1988;Field, Healy, & LeBlanc, 1989;Keener, Zeanah, & Anders, 1988;Scott & Richards, 1990;Zeanah, Keener, Anders, & Levine, 1986). Richman (198 1) reported that mothers of 1-to 2-year-old sleep-disturbed infants exhibited more psychopathology than mothers of control infants.…”
Section: The Parent Context: Personality and Attributionsmentioning
confidence: 99%
“…Studies of the importance of supportive relationships to parenting fall into two primary categories: those that explore the effects of general social support provided by others, and those that focus more on parents' own relationship history and comfort with establishing interpersonal relationships (attachment style). This research generally finds evidence that parents who have sufficient positive social support, both in terms of perceived and received support (Abidin 1992;Andresen and Telleen 1992;Cutrona and Troutman 1986;Kotchick et al 2005), and who have secure working models of attachment (e.g., Bowlby 1973;Feeney 2002;Belsky et al 1986;Rholes et al 1995) have better relationships with their children and better parenting skills, as measured across a variety of domains.…”
Section: Introductionmentioning
confidence: 99%